Value‐Added Per Share (VAPS): A Value‐Relevant Corporate Performance Metric. Issue 1 (24th April 2021) - Rajgopal, Shivaram; Rappaport, Alfred
Abstract : The authors introduce Value Added Per Share (VAPS) as a value‐relevant metric that is intended to complement earnings per share (EPS) in helping corporate managers and analysts understand and overcome the limitations of GAAP‐based reporting. VAPS discounts a firm's past and projected cash flows at its "cost of capital, " allowing companies to avoid the subjective accounting accrual process and other practices that often make EPS misleading. A company's VAPS is calculated in three main steps: (1) estimate the change in the capitalized value of after‐tax operating cash flow by taking the net change (plus or minus) of the firm's operating cash flow after taxes and dividing that number by the firm's cost of capital; (2) subtract total investment expenditures; and (3) divide by the number of shares outstanding. By capitalizing the change in after‐tax operating cash flow, one finds the net change in a firm's current operations value. By subtracting investment expenditures from that change in current operations value, the analyst gets a clearer picture of the benefit to shareholders net of the funds used to create that benefit. Consistent with basic theory, VAPS is positive when a company earns a return at least equal to its cost of capital and negative otherwise. Because of their fundamental differences, EPS and VAPS are likely to send different signals, and VAPS is expected to provide greater insight into stock price changes. The authors provide the findings of statistical tests showing the superior explanatory power of VAPS and recommend that companies publish statements of VAPS along with standard GAAP results, especially since the former can be readily calculated using the available income statement, balance sheet, and cash flow statement data.